Degree of risk of bias in randomized controlled trials: does it have an impact on root coverage outcomes? (2021)
ObjectiveImprovementovertime inmean (MRC)andcompleterootcoverage(CRC) reportedin randomized controlled trials (RCTs) has been documented. Our objective was toassess the effect that the ROB has on relevant outcomes reported in RCTsevaluating the efficacy of a commonly performed root coverage procedure.MethodsRCTs that involved the use of a bilaminar technique of coronally advancedflap withconnective tissue graft were selected. The following data were extracted: MRC,CRC, whether conflict of interest was addressed (yes/no), adequacy of randomsequence generation, allocation concealment, and blinding of outcome assess-ment. Trials were categorized into four groups as per different time periods: beforeConsolidated Standards of Reporting Trials (CONSORT) (before 1996), CONSORT(1997 to 2001), CONSORT 2001 (2002 to 2010), and CONSORT 2010 (2011 to2019). Differences between group means were assessed using statistical analyses.ResultsThe search yielded a total of 47 RCTs published between 1993 and 2019 that metthe inclusion criteria. A trend toward lower ROB over time in the selected RCTswas observed. However, differences in MRC and CRC with respect to the degreeROB of included trials were not significant.ConclusionsDegree of ROB did not influence MRC and CRC reported in the RCTs included inthis investigation. Thisfinding suggests that the observed improvement of clinicaloutcomes over time should be attributed to other factors, such as refinement ofsurgical techniques.